Adapting individual Cognitive Stimulation Therapy (iCST) for delivery by a touch-screen application for people with dementia - Rai, Harleen Kaur (2021)
Introduction: people with dementia may benefit from technology to enhance their quality of life (QoL), reduce social isolation and potentially improve cognition. Adapting existing interventions to digital platforms is a promising approach with prospective benefits. Group Cognitive Stimulation Therapy (CST) for people with dementia can benefit cognition and QoL. Individual CST (iCST) is delivered by a carer at home and can improve the relationship quality between the person with dementia and carer, and the QoL of carers. Given the lack of technological resources for the mental stimulation and engagement of people with dementia, there are potential benefits of combining iCST with touch-screen technology, which include improving global accessibility to iCST.